Answers

2016-04-12T10:21:09+05:30
By using distributive law
 ax(b+c)  = axb + axc
a) 18 x[7+(-3)] = 18x7  + 18 x (-3)
      18 x 4          = 126 - 54
          72     =  72     so it is true
b) -21 x [-4 + (-6)] = -21 x -4  + -21 x -6
      -21 x -10          = 84  +  126
             210             = 210     so this is also true   (- x - = +  & - x + = -)
0
2016-04-12T11:43:59+05:30
A) 18 x [7+(-3)]        =       [18 x 7 ] + [18 x (-3)]
     18 x [7-3]            =               126 + [-54]
     18×4                   =                126 -54
       72                     =                     72    
Hence verified 
b) (–21) × [(– 4) + (– 6)]      =         [(–21) × (– 4)] + [(–21) × (– 6)]
        -21 x [- 4 -6]                =                [-21 x -4]  + [-21 x -6]
      (-21) x (-10)                   =                          84  +  126
             210                         =                              210 
Hence verified
0